Recrutamento de populações leucocitárias induzido pela administração intraperitoneal de eotaxina em camundongos normais e deficientes em 5-lipoxigenase e na produção de eosinófilos - Arcanjo, Luiz Carlos Gondar (2010)
In previous studies of ovoalbumin-sensitized mice, our group provided evidence of an important link between the actions of eotaxin, a chemokine with known selectivity for the eosinophil lineage, and the activity of 5-lipoxygenase (5-LO), the enzyme required for generation of potent inflammatory mediators, such as Leukotriene B4 (LTB4), a chemoattractant and activator for neutrophils, eosinophils and mononuclear phagocytes, and the cysteinyl-leukotrienes, important in the pathophysiology of asthma. We have here reevaluated the relationship of eotaxin to 5-LO, using naive mice and a combination of pharmacological (inhibition of the 5-LO pathway), genetical (use of 5-LO deficient mice, or mice lacking eosinophils due to deletion of a high-affinity binding site in the promoter region of the GATA-1 gene) and immunological approaches (transfer of purified eosinophils into eosinophil-deficient hosts). Murine recombinant eotaxin, administered IP, induced significant accumulation of inflammatory cells in the peritoneal lavage fluid, relative to controls injected with vehicle (RPMI 1640 medium), at 50 and 100 ng/cavity, but not at lower doses. This effect was observed E 2h, 4h, 12h and 24 h after eotaxin administration. Eosinophil recruitment was significant at all these time points, with maximum at 4 h. It was followed by accumulation of neutrophils, significant at 4 and 12 h, and mononuclear cells (mostly macrophages), significant at 4, 12 and 24 h, both reaching maxima at 4 h, with average counts respectively 8, 2 and 9,9 -fold larger than those of eosinophils. Similar observations were made whenever significantly neutrophil or mononuclear cell recruitment was detected. In 5-LO deficient (ALOX) mice, there was no eosinophil recruitment, and neutrophil accumulation was significantly reduced, in contrast to the wild-type (PAS) controls of the same genetic background. In Balb/c mice, the effects of eotaxin on the accumulation of eosinophils, neutrophils and mononuclear cells were abolished by pretreatment with MK886, which prevents activation of 5-LO, in contrast to the recruitment observed in mice given vehicle. In eosinophil-deficient mice, eotaxin recruited neither neutrophils nor mononuclear cells, in contrast to controls of the same genetic background (Balb/c). Reconstitution of eosinophil-deficient mice with purified Balb/c eosoinophils restored the recruitment of both neutrophils and mononuclear phagocytes, with a major impact on the latter. Overall, these data indicate that: a) the administration of recombinant eotaxin in nonsensitized mice does not selectively attract eosinophils; b) eosinophils, neutrophils and macrophages are recruited by a 5-LO-dependent mechanism; c) neutrophils and macrophages are recruited by an eosinophil-dependent mechanism. In conclusion, the eosinophil, in these experimental conditions, mediates the recruitment of other leukocyte subpopulations, in what may be a hitherto unexplored physiological role for this cell type.